Psychosocial determinants of leisure-time physical activity among adults in omdurman city, Sudan: Reasoned Action Approach - Almutaz M. Idris; Aisha O. Yousif; Sami M. Assil; El-Fatih (Elsevier, 2022)
Objectives: The level of physical activity among adult in Sudan is low. The purpose of this study used the Reasoned Action Approach to investigate the psychosocial determinants of Leisure-Time Physical Activity Behaviour (LTPA) of Sudanese adults. Study design: This was a cross-sectional study design among adults in Omdurman city in Sudan. Methods: A 378 participants (229 male and 149 female) completed a questionnaire to identify intention, attitude, subjective norms, perceived behaviour control about LTPA and actual behaviour. The relationship between studied determinants were examined using different statistical methods. Results: In all participants, 13% had at least 150 min of moderate-intensity LTPA per week. Analysis revealed that intentions (β = 0.26) along with perceived behaviour control (β = 0.19) predicted LTPA and accounted for 12% of the variance in LTPA behaviour. Attitude (β = 0.39), subjective norms (β = 0.18), and perceived Behaviour control (β = 0.11) were associated with intention to perform LTPA. They explained 22% of the variance in intentions. Conclusion: consistent with RAA expectations, determinants of the intentions and LTPA behaviour were identified. Findings suggest interventions promoting LTPA in Sudanese adults should increase intention, create a positive attitude, build conducive social norms and raise the perception of control over the actual LTPA behaviour.